2021
DOI: 10.1007/s11628-021-00470-9
|View full text |Cite
|
Sign up to set email alerts
|

Cross-country differences in drivers of female necessity entrepreneurship

Abstract: This paper analyzes the drivers of female necessity entrepreneurship using a sample of 59 countries, with data sourced from the 2018–2019 global entrepreneurship monitor (GEM). It develops a theoretical framework describing how post-secondary education, startup skills, fear of failure, knowing another entrepreneur, entrepreneurial intentions, and hiring expectations act as drivers of female necessity entrepreneurship. Using qualitative comparative analysis, two models are tested to explain the presence and abs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 85 publications
0
20
0
1
Order By: Relevance
“…The decision to use this methodology was primarily based on its suitability for the study of phenomena in the social sciences because it allows for equifinality and multifinality (Gerrits and Pagliarin, 2021). It has been widely used in business research and has the advantage of allowing for causal multiplicity (Sendra-Pons et al, 2022a). Hence, it can offer a useful way of studying reality.…”
Section: Methodsmentioning
confidence: 99%
“…The decision to use this methodology was primarily based on its suitability for the study of phenomena in the social sciences because it allows for equifinality and multifinality (Gerrits and Pagliarin, 2021). It has been widely used in business research and has the advantage of allowing for causal multiplicity (Sendra-Pons et al, 2022a). Hence, it can offer a useful way of studying reality.…”
Section: Methodsmentioning
confidence: 99%
“…En cuanto al género, el porcentaje de empresarias que planifican a largo plazo resulta ligeramente inferior al de los empresarios. Este resultado podría relacionarse con las menores aspiraciones emprendedoras de las mujeres, las cuales inician un negocio, más por cuestiones de necesidad que de oportunidad, ante la falta de alternativas de empleo satisfactorias (Sendra-Pons et al, 2021). Sin embargo, ellas sienten más confianza para acudir a los inversores, en mayor medida que sus homólogos masculinos.…”
Section: Actitudes Financierasunclassified
“…Individuals with high fear of failure tend to regard entrepreneurial activities as threats rather than opportunities. As a result, fear of failure weakens individual entrepreneurial intention and discourages entrepreneurial activity (Kickul et al , 2009; Sendra-Pons et al , 2022). Johnson and Powell (1994) found that women have a lower risk tendency than men and are more likely to be pessimistic about the outcomes of new ventures.…”
Section: Literature Review and Research Frameworkmentioning
confidence: 99%